IMPROVING THE SYSTEM OF STATE FINANCIAL CONTROL OVER THE USE OF BUDGET FUNDS IN BUDGET ORGANIZATIONS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article focuses on enhancing the current framework of state financial control to ensure efficient and transparent use of budgetary resources in public sector organizations. With increasing pressures on public finances and the need for accountability, it is essential to scrutinize how budget funds are allocated, managed, and utilized. Implementing robust audit processes that regularly assess financial practices within budget organizations, ensuring compliance with legal and regulatory standards. Utilizing modern technology to promote open data initiatives, enabling stakeholders to monitor public spending and facilitating civic engagement in budgetary processes. Providing training and resources for budget managers and financial officers to enhance their understanding of effective financial management practices, risks, and controls. Establishing clear responsibilities and consequences for mismanagement of funds, fostering a culture of accountability within budget organizations. By improving these systems, the integrity of public sector financial management can be fortified, ultimately leading to more effective and efficient use of taxpayer money, thereby boosting public trust in government institutions.